Linkages of natural gas and oil futures prices on the American and European derivatives market - Łęt, Blanka (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
In recent years, the world natural gas market is changing mainly due to the wid-er access to LNG (Liquefied Natural Gas). This technology allows to trade between the market participants all over the world. The natural gas prices on the American and European market are benchmarked to Henry Hub and National Balancing Point (NBP) natural gas. The goal of this paper is to investigate whether the listings of natural gas in the derivatives markets are linked and to analyse the relationship between natural gas and crude oil prices. We show that the probability distribution of returns is not normal and that there is a strong ARCH effect. We use multivariate GARCH model to describe the linkages between several series. We take into account two return series of natural gas futures contracts (Henry Hub and National Balancing Point) and two returns series of crude oil futures contracts (West Texas Intermediate and Brent) to measure the strength of linkages across two commodity markets of the most important fossil fuels
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 482, s. 158-168
Keywords: natural gas; crude oil; derivative market; constant conditional correlation model; gaz ziemny; ropa naftowa; rynek terminowy; model stałych korelacji warunkowych